The fliK Gene Is Required for the Resistance of Bacillus thuringiensis to Antimicrobial Peptides and Virulence in Drosophila melanogaster - Attieh, Zaynoun; Mouawad, Carine; Rejasse, Agnès; Jehanno, Isabelle; Perchat, Stéphane; Hegna, Ida K.; Økstad, Ole A.; Kallassy Awad, Mireille; Sanchis-Borja, Vincent; El Chamy, Laure (Frontiers in Microbiology, 2020)
Antimicrobial peptides (AMPs) are essential effectors of the host innate immune system and they represent promising molecules for the treatment of multidrug resistant microbes. A better understanding of microbial resistance to these defense peptides is thus prerequisite for the control of infectious diseases. Here, using a random mutagenesis approach, we identify the fliK gene, encoding an internal molecular ruler that controls flagella hook length, as an essential element for B. thuringiensis resistance to AMPs in Drosophila. Unlike its parental strain, that is highly virulent to both wild-type and AMPs deficient mutant flies, the fliK deletion mutant is only lethal to the latter’s. In agreement with its conserved function, the fliK mutant is non-flagellated and exhibits highly compromised motility. However, comparative analysis of the fliK mutant phenotype to that of a fla mutant, in which the genes encoding flagella proteins are interrupted, indicate that B. thuringiensis FliK-dependent resistance to AMPs is independent of flagella assembly. As a whole, our results identify FliK as essential determinant for B. thuringiensis virulence in Drosophila and provide new insights on the mechanisms underlying bacteria resistance to AMPs.